2021
DOI: 10.1051/e3sconf/202124803041
|View full text |Cite
|
Sign up to set email alerts
|

Research on Risk Management of Green Supply Chain of Prefabricated Buildings Based on QCA

Abstract: In the context of sustainable development, green supply chain, as a whole-process environmental management model, provides a good implementation path for the development and utilization of prefabricated buildings. However, the green supply chain operation of prefabricated buildings in a complex social network environment involves many risk factors, which seriously affect the realization of the green supply chain management goals. This research first identifies risk factors based on the perspective of stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Hsu et al [16] discussed the influence of the schedule deviation on the supply chain of prefabricated buildings, and established a mathematical model that could choose the optimal production and transportation scheme. Yang et al [17] adopted the fuzzy set qualitative comparative analysis method to analyze the green supply chain risk of prefabricated buildings from a holistic perspective, and fully considered internal and external links to help all participants in the supply chain to avoid risks. Sun et al [18] analyzed the risk transmission effect, established a risk network model combining the complex network theory, and proposed the risk immunization strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hsu et al [16] discussed the influence of the schedule deviation on the supply chain of prefabricated buildings, and established a mathematical model that could choose the optimal production and transportation scheme. Yang et al [17] adopted the fuzzy set qualitative comparative analysis method to analyze the green supply chain risk of prefabricated buildings from a holistic perspective, and fully considered internal and external links to help all participants in the supply chain to avoid risks. Sun et al [18] analyzed the risk transmission effect, established a risk network model combining the complex network theory, and proposed the risk immunization strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of risk assessment, Ming et al [19] comprehensively identified various risks in the investment stage of prefabricated buildings in China by establishing a system dynamics model and quantitatively analyzed investment risks; Luo et al [20] came to the conclusion that prefabricated construction projects are an actual case to study the supply chain risk and the interaction between supply chain risks and find the biggest risk factors affecting the prefabricated construction supply chain; Too et al [21] put forward a framework for the impact of carbon emissions during the evaluation items in the planning, delivery, closing, and operation. This study considers the impact of carbon emissions on the entire construction activity and puts it in environmental risks for analysis and research; Yang and Ren [22] used the fuzzy comparative analysis method to analyze the risks of prefabricated building green supply chain from the overall perspective and proposed targeted measures to avoid risks. In terms of risk management, Tah and Carr [23] proposed a knowledge management database for risk management of engineering supply chains in view of the defects in the process of engineering project risk management; Hsu and Aurisicchio [24] proposed adding mathematical models to using a risk avoidance model for prefabricated buildings; Shojaei and Haeri [25] conducted scientific guidance and evaluation on the risk management of the prefabricated building project supply chain based on gray correlation.…”
Section: Prefabricated Building Supply Chain Risk Managementmentioning
confidence: 99%